The Present Day Situation on Residential Real Estate Market in Russia - A. A. Volkov (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
Housing market in Russia is one of the most important indicators of economy standing. Accelerated functioning of the majority of fields and branches of regional economy is provided by its development. Provision of affordable housing, which meets today’s requirements of comfort and safety, is a priority of social and economic policy of our country. On this basis the author analyzed key indicators characterizing the current situation on residential real estate market in the Russian Federation and federal areas. They are as follows: provision of the population with residential RE, commissioning of RE, the number of apartments of completed construction, the volume of damaged housing, average prices on market, etc. As a result of the analysis the following trends were identified: by figures of housing area per one dweller Russia is lagging behind developing and industrial countries; commissioning of residential RE has dropped and prices on 1 m2 have risen. Methodological foundation of the research was formed by economic and statistic methods, synthesis, systematic analysis and comparative analysis. For this article the author used academic literature by home and overseas authors and information of the Federal Service of State Statistics and the Bank of Russia. The findings of the article can be useful for authorities in making managerial decisions and for academic community dealing with issues of residential RE market.